Development of Nearpod-Based Interactive Learning Media on Environmental Pollution Materials - Hesti Gustini; Yayat Ruhiat; Lukman Nulhakim (Postgraduate, University of Mataram, 2023)
This study aims to develop learning media using the Nearpod application on environmental pollution material for class VII in SMP/MTs. This type of research is development research using the ADDIE model, which consists of several stages, namely analysis, design, development, implementation, and evaluation. This research was conducted until the stage of development (development). Based on the results of the stages carried out with the ADDIE model, it can be concluded that Nearpod-based interactive learning media can then validate media experts and material experts. So that it can be implemented in the science learning process, especially environmental pollution material.